2020
DOI: 10.3389/fgene.2020.00253
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Analysis to Evaluate the Prognostic Value of Signature mRNAs in Glioblastoma Multiforme

Abstract: Background: Gliomas are the most common intracranial tumors and are classified as I-IV. Among them, glioblastoma multiforme (GBM) is the most common invasive glioma with a poor prognosis. New molecular biomarkers that can predict clinical outcomes in GBM patients must be identified, which will help comprehend their pathogenesis and supply personalized treatment. Our research revealed four powerful survival indicators in GBM by reanalyzing microarray data and genetic sequencing data in public databases. Moreove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 46 publications
7
11
0
Order By: Relevance
“…We found that high expression of GNG5 promotes the activation of a series of cancer-related signaling pathways (Figure 6). Similar interactions have been described previously; for example, the ECM-receptor interaction is involved in the proliferation and invasion of cancer cells [37,38], and focal adhesion is involved in the metastasis and invasion of cancer cells [39]. Additionally, the toll-like receptor promotes the immune evasion of glioma by down-regulating the MHC II molecules in microglia [40], and cell adhesion molecules and the nod-like receptor play a signi cant role in the proliferation, invasion, and metastasis of glioma cells [41][42][43][44].…”
Section: Discussionsupporting
confidence: 70%
“…We found that high expression of GNG5 promotes the activation of a series of cancer-related signaling pathways (Figure 6). Similar interactions have been described previously; for example, the ECM-receptor interaction is involved in the proliferation and invasion of cancer cells [37,38], and focal adhesion is involved in the metastasis and invasion of cancer cells [39]. Additionally, the toll-like receptor promotes the immune evasion of glioma by down-regulating the MHC II molecules in microglia [40], and cell adhesion molecules and the nod-like receptor play a signi cant role in the proliferation, invasion, and metastasis of glioma cells [41][42][43][44].…”
Section: Discussionsupporting
confidence: 70%
“…Similar interactions have been described previously; for example, the ECM-receptor interaction is involved in the proliferation and invasion of cancer cells [35,36], and focal adhesion is involved in the metastasis and invasion of cancer cells [37]. Additionally, the toll-like receptor promotes the immune evasion of glioma by down-regulating the MHC II molecules in microglia [38], and cell adhesion molecules and the nod-like receptor play a signi cant role in the proliferation, invasion, and metastasis of glioma cells [39][40][41][42].…”
Section: Discussionsupporting
confidence: 70%
“…6). Similar interactions have been described previously; for example, the ECM-receptor interaction is involved in the proliferation and invasion of cancer cells [35,36], and focal adhesion is involved in the metastasis and invasion of cancer cells [37]. Additionally, the toll-like receptor promotes the immune evasion of glioma by down-regulating the MHC II molecules in microglia [38], and cell adhesion molecules and the nod-like receptor play a signi cant role in the proliferation, invasion, and metastasis of glioma cells [39][40][41][42].…”
Section: Discussionsupporting
confidence: 70%